CONSTRUCCIÓN DE UNA BIBLIOTECA GENÓMICA DE Coffea Arabica Var. COLOMBIA Y EVALUACIÓN CON UNA SECUENCIA HOMÓLOGA A UBIQUITINA (2004)
A Lambda FIX II genomic library consisting of 1,33x106 pfu/ml with an average DNA insert size of 15 kb was constructed from Coffea arabica var  Colombia DNA. The haploid coffee genome was represented 3,7 times approximately. The library was evaluated with a coffee PCR product (primers InhF - R631) which has a high homology with Arabidopsis thaliana and Oriza sativa ubiquitin like sequences. Two recombinant clones were  identified (cof-ubi1 y cof-ubi2) that hybridized with the ubiquitin like probe.The results indicate that the library can be used to isolate new sequences of interest in genomic mapping and may contribute in expression and gene  regulation studies.